Development Of Green Curtain Noise Barrier Using Natural Waste Fibres - Ahmad Yusuf, Ismail; Norshadatulakmar, Mat Shadid; Aliah Mastura, Mohd Nizam (Penerbit Akademia Baru, 2016)
Noise pollution is one of the major problems in industry. Noise, which is commonly known as undesired sound, comes from numerous industrial machineries and very harmful to the human body. One of the simplest ways to solve this problem is by employing a noise barrier or partition. Current noise barrier are mostly made from synthetic materials which apparently causes another serious problem to the human health. Investigation on the alternative acoustic materials particularly natural fibres has therefore been widely conducted by researchers to solve the problem. This paper introduces natural fibres i.e. paddy straw and coconut fibres as an additional acoustic material to form an eco-friendly noise barrier system. The natural fibre is mixed with synthetic fibre to form a dissipative layer inside the barrier to absorb sound energy. The sample is then tested inside an anechoic chamber to measure its sound pressure level, which is the most common considered value in industrial noise. From the experimental results, it is found that the natural fibres give considerable performance and very potential to substitute the synthetic fibres.